Territorial obstinacy - Pinto, Hugo (2019)
The last decade witnessed a global economic crisis with unbalancing effects in national and regional economies. Despite the importance of territorial capabilities to face adversity, the “territory” seems to be fading away from public policy. That was clear with the implementation of austerity measures that stimulated centralization of financial resources but also with the relevance given to innovation as the main purpose of development, particularly in European Union with the smart specialization rationale. The current issue of Regional Science – Policy and Practice is devoted to a selection of papers presented at the International Conference on Local Development (Faro, Portugal, 2017). This conference was part of the 4th Edition of the Award on Territorial Development, a distinction that intends to call attention on the opportunities of endogenous and bottomup initiatives for territorial development.